Analytical Framework to Model Reconfigurable Metasurfaces including Lumped Elements. - Pérez-Escribano, Mario; Moreno-Rodríguez, Salvador; Molero, Carlos; Valenzuela-Valdés, Juan Francisco; Padilla, Pablo; Alex-Amor, Antonio (IEEE Transactions on Circuits and Systems II: Express Briefs, 2023)
This manuscript introduces an analytical framework for the design of reconfigurable metasurfaces rooted in 2D periodic structures. Incorporating lumped elements into the model streamlines the design process for such devices, offering significantly improved efficiency compared to designs reliant on full-wave software. The theoretical framework, founded on Floquet modal expansions, also guarantees robust performance even under oblique incidence conditions, far beyond the onset of the first grating lobe. In practical applications, an absorber has been devised by integrating a resistor into the model. Nevertheless, circuit analysis extends the possibilities for crafting more intricate structures utilizing diodes or tunable varactors, enabling the design of phase shifters, polarizers, and reconfigurable intelligent surfaces (RIS).
Keywords: Telecomunicaciones; Conductores eléctricos; Fotónica; Analytical framework; Lumped elements; Metasurfaces; Floquet expansion; Oblique incidence; Reconfigurable